Updating the Botany Coordination of the Museu Paraense Emílio Goeldi throughout the 150 years - Secco, Ricardo de S. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
An updated historical account about the origin and activities of the Botany Division of the Museu Paraense Emílio Goeldi (COBOT) throughout the 150 years of the institution is given here. It highlights the periods of Jacques Huber, Adolpho Ducke, and Paulo Cavalcante, followed by the advances introduced by João Murça Pires, and continuing with the arrival of new projects and activities in the 20th and 21st centuries.